Analysis and Design of Microwave Dielectric Heating with Curved Plate Applicator for Deep Hyperthermia in Breast Cancer Treatment - Kotchapradit, Supawat; Thongsopa, Chanchai; Thosdeekoraphat, Thanaset (Společnost pro radioelektronické inženýrství, 2019)
This paper presents microwave hyperthermia treatment using dielectric heating techniques with the curved plate applicator. The 3D breast phantom model simulation was used to investigate heat distribution. The microwave heating equation was employed to focus the power loss density in the deep breast phantom tissues that consists of skin, fat, and tumor, 2D maximum (W cm-3) are 5.67, 11.92, and 8.42 for tumor size as 10 mm, 16 mm, and 30 mm, respectively. The dielectric constant and loss factor of tumor tissue provides 55.25 and 19.8, respectively. The power loss density was analyzed was excited by microwave power signal generator 2450 MHz inside of the breast phantom. This heating technique was implemented based on the electric field generated by the curved plate applicator, which is designed by a series resonance circuit with an LC matching element. Simulations revealed that the heating focused area could be targeted into the internal tumor. The measurement of dielectric properties at 24°C was performing by open-ended coaxial dielectric probe kit (N1501A, Keysight Technology) connected to a vector network analyzer (E5071C, Keysight Technology) that can be operated in the range of 1 – 10 GHz. The heat distribution was measured in agar phantom as a surrogate tumor tissue using IR cameras (U5857A True IR, Keysight Technology). The parameters of microwave DC input power 120 W, efficiency about 20 % and get microwave power at 24 W to generate a stabilized temperature between 39 – 42°C.
Keywords: Dielectric applicator; microwave treatment; deep hyperthermia